Determination of Nifedipine drug in Pure and Pharmaceutical Preparations by Normal Flow Injection Analysis using Sulfamethaxazole Drug as Chromogenic Reagent - Allaa Hussein Mhdi, Sadeem Subhi Abed (Pakistan Journal of Medical & Health Sciences, 2022)
A highly sensitive and accurate spectrophotometric method including Technique ( Normal Flow injection analysis have been used for determined Nifedipine (NIF) drug in pure and dosage forms. This approach based on the response of drug with diazotized sulfamethoxazole (SMZ) to form colore product after diazotization of reagent and coupling reaction with drug The coloured chromogen suggests absorption maximum at 496 nm. The method of the line conditions of response had been investigated by (1) invariable chemical approach, by optimizing the impact of experimental variables (special bases, reagent awareness, and reaction time), (2) physical methods including the effect of three experimental factors (injection loop length , reaction coil ,flow rate and reaction time). The results gave Beer’s law is obeyed over the awareness range 2-180 μg. ml-1 with an excellent determination coefficient (r2= 99.97) and molar absorptivity 3428.714. The stoichiometry of the resulting azo dye has been also worked out and it is found to be 1:1 Nif: SMZ. This method has been carried out successfully for the determination of Nifedipine in pharmaceutical preparations (tablets). Keywords: Nifidipine , flow injection analysis, spectrophotometry, Sulfamethoxazol ، diazotization.